Population and development issues in Bangladesh : national plan of action based on ICPD'94 recommendations - Barkat, Abul.; Howlader, Sushil Ranjan; National Committee for the Implementation of the Recommendations of the International Conference on Population and Development (Bangladesh) (Dhaka : Ministry of Health and Family Welfare, Govt. of the People's Republic of Bangladesh, 1997)
Theme papers presented at a technical workshop held on December 17, 1996.
Includes bibliographical references.
Keywords: Bangladesh -- Population; Bangladesh -- Social policy